Immunogenomic Landscape and Immune-Related Gene-Based Prognostic Signature in Asian Gastric Cancer - Mao, Chenchen; Ma, Liangliang; Huang, Yingpeng; Yang, Xinxin; Huang, He; Cai, Wentao; Sitrakiniaina, Andriamifehimanjaka; Gu, Ruihong; Xue, Xiangyang; Shen, Xian (Frontiers in Oncology, 2021)
Background: Asians have the highest incidence of gastric cancer (GC), and the prognosis of Asian GC is poor. Furthermore, the therapeutic for Asian GC is limited because of genetic heterogeneity and screening difficulty in early stage. This study aimed to develop an immune-related gene (IRG)-based prognostic signature and to explore prognosis-related regulatory mechanism and therapeutic target for Asian GC. Methods: To elucidate the prognostic value of IRGs in Asian GC, a comprehensive analysis of IRG expression profiles and overall survival times in 364 Asian GC patients from the Asian Cancer Research Group (ACRG) and The Cancer Genome Atlas (TCGA) databases was performed, and a novel prognostic index was established. To further explore regulatory prognosis mechanisms and therapeutic targets, a tumor immunogenomic landscape analysis, including stromal and immune subcomponents, cell types, panimmune gene sets, and immunomodulatory genes, was performed. Result: Our analysis allowed the creation of an optimal risk assessment model, the Asian-specific IRG-based prognostic index (ASIRGPI), which showed a high accuracy in predicting survival in Asian GC. We also developed an ASIRGPI-based nomogram to predict the three- and five-year overall survival (OS) of Asian GC patients. The impact of the ASIRGPI on the worse prognosis of Asian GC was possibly related to the stromal components remodeling. Specifically, TGFβ gene sets were significantly associated with the ASIRGPI and worse prognosis. Immunomodulatory gene analysis further revealed that TGFβ1 and EDNRB may be the novel potential therapeutic targets for Asian GC. Conclusions: As a tumor microenvironment-relevant gene set-based prognostic signature, the ASIRGPI model provides an effective approach for evaluating prognosis of Asian GC, and may even prolong OS by enabling the selection of individualized therapy with the novel targets.